A Critical Study of Poverty and Exploitation in Sherman Alexie’s True Diary: The Devastating Effects of Poverty and Exploitation on Native Americans in Sherman Alexie's Works (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Alexie superbly narrates and portrays daily life of Native Americans which is reflected and filled with poverty and exploitation. His characters were exploited by the white for a long time. They were debarred from their land. Their law and unstable income add to their pitiable plights. They finally lose their last hope to recover from their miserable condition. Alexie painted Reservation a horrid place haunted by horrid history. As I have shown already in the former chapters that the protagonists don’t want to live on Reservation. They wanted to go in the White school and wanted to settle in Seattle. Far from being a stimulating environment, the Reservation community keeps its members from succeeding and achieving their dreams. The rare individuals who persevere are rejected and their endeavor makes them outcasts. Trying hard and having talent are virtues that are regarded as flaws by the majority of the Reservation people. Reservation appears in the works of Alexie, as a place where poverty, unemployment, alcoholism suffering and violence are common among Americans Indians. The feeling of poverty is pervasive in Natives that are set on Reservation. Aothor's Reservation characters live in poorly built HUD houses and surplus commodity food on the daily basis. Many of Alexie's characters are hopeless and despair. Very often the atmosphere of novels and short stories is bleak and future of the characters seems to be deteriorated.